Biological Control of Damping- off and Wilt of Albizia lebbek Seedlings Using Plant Extracts - Harsh, N. S. K. (Indian Forester, 1998)
Biological control of damping-off and wilt disease of Albizia lebbek seedlings caused by Fusarium pallidoroseum has been worked out using some plant extracts. Leaf extract of Vitex negundo and plant extract of Cuscuta reflexa were found effective in inhibiting the conidial germination and mycelial growth of the pathogen and also in controlling the disease in field